Informality and the Playing Field in Vietnam's Business Sector - Tenev, Stoyan; Carlier, Amanda; Chaudry, Omar; Nguyen, Quynh-Trang (Washington, DC: World Bank and the International Finance Corporation, 2013)
The development story in Vietnam in recent years has been one of remarkable progress (Dollar 2002). Over the 1990s, the economy doubled and the incidence of poverty declined by half. Although these are indeed notable achievements, they are but the first steps across a difficult terrain. About 30 million people, or more than a third of the total population, continue to live in poverty, and 25 million, or about 60 percent of the labor force, are either underemployed or unemployed. To create jobs for the unemployed, underemployed, and new additions to the work force, Vietnam will have to double the economy again by the end of the decade, but this cannot happen unless both the level and the quality of investment increase substantially. According to World Bank estimates, average total investment must reach 30 percent of gross domestic product (GDP) by 2010, which represents a 5 percent increase over the 1990s, while average productivity will have to be about 40 percent higher (World Bank 2001). To achieve these objectives, Vietnam needs to encourage the private sector to contribute more to economic growth. This will require significant improvements in its business environment.